The Legal Implications of Music Royalty Dispute Resolution through Mediation: A Case Study of Mie Gacoan-LMK SELMI - Towoliu, Nadyne Althea Alandia; Mori, Momoko; Haningati, Gumilang Chandra Shasmita; Rachmadani, Resita (Journal of Law, Politic and Humanities, 2025)
Copyright over songs and/or music constitutes an exclusive right inherent to the author and related rights holders, particularly economic rights in the form of royalty payments for every commercial use. Such provisions are explicitly regulated under Law No. 28 of 2014 on Copyright and Government Regulation No. 56 of 2021 on the Management of Copyright Royalties for Songs and/or Music. This research aims to analyze the legal implications of resolving royalty disputes between the National Collective Management Organization (LMKN) and PT Mitra Bali Sukses, the owner of the Mie Gacoan trademark, through mediation. Employing a normative juridical method with statutory and case approaches, the findings indicate that mediation produced an agreement stipulating royalty payments of approximately IDR 2.2 billion and a license valid until the end of 2025. The legal implications include the creation of a new legally binding obligation (settlement agreement), the elimination of potential lawsuits as long as the parties comply with the agreement, and the assurance of fulfilling authors’ economic rights through royalty distribution by LMKN. Nonetheless, issues remain in the form of weak public dissemination, negative public perceptions, and potential overlaps of authority between LMK and LMKN. Accordingly, mediation can be considered an effective mechanism for resolving copyright disputes, yet it still requires oversight, transparency, and institutional harmonization to realize legal certainty and optimal protection for authors.